Evaluation of a school-based intervention to promote mental health of refugee youth in Sweden (The RefugeesWellSchool Trial): study protocol for a cluster randomized controlled trial - Natalie Durbeej; Serena McDiarmid; Anna Sarkadi; Inna Feldman; Raija-Leena Punamäki; Reeta Kankaanpää; Arnfinn Andersen; Per Kristian Hilden; An Verelst; Ilse Derluyn; Fatumo Osman (Trials, 2021)
Abstract Background Sweden is home to a large and growing population of refugee youths who may be at risk of mental health problems such as post-traumatic stress disorder (PTSD). Thus, there is a need for interventions that address mental health problems in these populations. Schools have been identified as an ideal setting for delivering such interventions as they offer a non-stigmatizing space and are often central to young refugees’ social networks. The RefugeesWellSchool trial in Sweden will investigate an intervention comprising two programmes: Teaching Recovery Techniques (TRT) and In-service Teacher Training (INSETT), delivered in a school setting, among refugee youth. TRT is a group-based programme for children and adolescents, informed by Trauma-Focused Cognitive Behavioral Therapy (TF-CBT). INSETT is a multi-module course for teachers providing information on trauma and the refugee experience to build teachers’ cultural competence and capacity for supporting refugee youths in schools. Methods This trial employs a cluster randomized-control design with two arms: (1) the intervention arm in which the TRT and INSETT programmes are offered (n = 350), (2) the wait-list control arm (n = 350) in which services are provided as usual until the TRT and INSETT programmes are offered approximately six months later. Data will be collected prior to the intervention, immediately following the intervention, and at three months post-intervention. Outcomes for the trial arms will be compared using linear mixed models or ANCOVA repeated measures as well as the Reliable Change Index (RCI). Discussion This study will provide knowledge about the effectiveness of an intervention comprising two programmes: a group-based programme for youth reporting symptoms of PTSD and a training course for teachers, in order to build their competence and ability to support refugee youths in schools. Trial registration ISRCTN, ISRCTN48178969 , Retrospectively registered 20/12/2019.